BAF complexes drive proliferation and block myogenic differentiation in fusion-positive rhabdomyosarcoma - Dominik Laubscher (Nature Portfolio, 2021)
Rhabdomyosarcoma (RMS) is a pediatric malignancy of skeletal muscle lineage with an aggressive subtype caused by translocations involving PAX3- /PAX7-FOXO1 chimeric transcription factors. Here the authors show that the BRG1-containing BAF complex is overexpressed and acts largely independently of the PAX3-FOXO1 chimera on chromatin to result in a myogenic differentiation blockade in this malignancy.